Nano-fiber based self-powered flexible vibration sensor for rail fasteners tightness safety detection. (November 2022) - Meng, Yan; Yang, Jiayi; Liu, Shuangshuang; Xu, Wei; Chen, Guobin; Niu, Zihao; Wang, Meiqi; Deng, Tao; Qin, Yong; Han, Mengdi; Li, Xiuhan
Abstract: Rail fasteners are the key components of railway tracks, and regular inspection of them is conducive to the safe operation of railway lines. In order to establish a real-time and efficient rail fasteners tightness safety detection system, a self-powered vibration sensor based on electrospinning nanofibers with high output performance TENG is proposed for daily safety inspection of rail fasteners. The power generation performance of the vibration sensor is characterized with the open-circuit voltage of 185 V, the short-circuit current of 5.68 μA cm −2, and the power density of 4.28 W m −2 under matching load. In addition, it also has excellent working stability, good environmental adaptability and fast response time (40 ms). Therefore, the vibration sensor can not only effectively collect rail vibration energy to achieve energy self-supply, but also accurately identify the tightness of rail fasteners according to the vibration characteristics, so as to ensure the safe operation of railway lines. The manufacturing process of the vibration sensor is convenient, economical and practical, and it is hoped to provide a meaningful detection method for maintaining the safety of railway lines. Graphical Abstract: Rail fasteners are the key components of railway tracks, and regular inspection of them is conducive to the safe operation of railway lines. In order to establish a real-time and efficient rail fasteners tightness safety detection system, a self-powered vibration sensor based on electrospinning nanofibers with high output performance TENG is proposed. The power generation performance of the vibration sensor is characterized with the open-circuit voltage of 185 V, the short-circuit current of 5.68 μA cm −2, and the power density of 4.28 W m −2 under matching load. It also has excellent working stability, good environmental adaptability and fast response time (4 ms). The vibration sensor can effectively collect rail vibration energy to achieve energy self-supply, and accurately identify the tightness of rail fasteners according to the vibration characteristics, so as to ensure the safe operation of railway lines. Fig. (a) Application scenario of the vibration sensor placed inside rail for rail fasteners tightness safety detection. (b) Schematic diagram of the vibration sensor. (c) SEM images of PVDF/BTO nanofibers. (d) X-ray diffraction spectrums of PVDF/BTO nanofibers. (e) Schematic diagram of the rail fasteners tightness safety detection system. (f) The relationship between voltage signals and looseness degree of rail fasteners. The real-time voltage signal (g) and LabVIEW interface (h) of rail fasteners tightness safety detection. ga1 Highlights: A high-performance self-powered nanofiber vibration sensor was developed to realize tightness safety detection of railway fasteners. SNVS with high output performance, fast response time and excellent working stability was constructed based on the electrospinning process. SNVS was successfully integrated into the rail to collect vibration energy and perform tightness safety detection of rail fasteners.